(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
For many years, inlays and onlays made of various materials have been considered by dentists as one of the best methods for restoring teeth with medium to large-area carious lesions (Christensen G.J., 1966). Until now, prosthetics were made using a plaster model, which was used directly to create the prosthesis or was digitally scanned to create a virtual model. Improvements in digital impression technologies have significantly simplified the process, increasing patient comfort and speed of procedures, as well as ensuring high quality of restorations (Logozzo S, Zanetti E.M., 2014; Beuer F, Schweiger J., 2008). In addition, the advantages of 3D digitalization include a reduction in the time required to obtain clinical impressions, which, according to recent data, has been reduced by 23 minutes compared to taking conventional impressions (Patzelt S.B, Lamprinos C, Stampf S, Att W., 2005). Intraoral scanners should provide not only high image resolution but also the ability to reproduce 3D images. Intraoral scanning can reduce potential distortions caused by the use of conventional impression materials and allow taking impressions of cavities, reducing material consumption. The introduction of CAD/CAM systems has led to an increase in the use of inlays instead of direct restorative technologies and materials; however, further research is needed to confirm the advantages of these systems (Pol CW, Kalk W., 2011; Santos M.J, Freitas M.C., 2016). Undoubtedly, marginal fit due to the presence of marginal gap and hyperextension control can lead to plaque accumulation (Goujat A, Abouelleil H., 2019), and this is one of the most important criteria for assessing the long-term functional success of the restoration (Pak H.S, Han J.S., 2010). The main reason for restoration failure is cement degradation, and subsequent microleakage can lead to periodontal tissue inflammation and secondary caries in the contact area (Zarauz C, Valverde A, Martinez-Rus F, Hassan B, Pradies G., 2016).